The Effect of STEM-Based Digital Teaching Materials on Light Wave Material on Student Learning Outcomes in Physics Learning - Rahmi, Lailatul; Ratnawulan, Ratnawulan (Universitas Negeri Padang, 2023)
Low student learning outcomes are due to teacher-centered learning and lack of use of digital materials. One way to solve this problem is the use of digital educational resources for STEM (science, technology, engineering, and math) topics. This study's objective was to ascertain the impact of her STEM-based digital material for light waves on student learning outcomes in a physics class. This method of research is the scientific method, that is, experimental research. The study design used is a straightforward experimental strategy (post-test only control strategy). The XI IPA class served as the study's entire population, and the samples used were from the XI IPA 3 control class and the XI IPA 4 experimental class. Data collection means use end-of-learning tests or post-tests. Data processors were performed using the IBM SPSS program version 29.0 with normality tests, homogeneity tests, and hypothesis tests (t-tests). Based on the outcomes of our research, we discovered that the obtained data are normally distributed with a level of 0.182 ≥ 0.05 for the control class and 0.073 ≥ 0.05 for the experimental class. For the homogeneity test, the levels are 0.073 ≥ 0.05, so the classes are homogeneous. On the other hand, for hypothesis tests or t-tests, the obtained sig (two-tailed) post-test is <0.001. This value is less than 0.005 and is based on the rejection criteria for Ho. The result of the pre-test t-test analysis is 0.164, which means that this value is greater than 0.05, so Ho is accepted. From this, we can conclude that his STEM-based digital teaching materials on light waves have an impact on students' learning outcomes in physics classes.